PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 43 PADANG - Artikel, Yuli; Nasution, Minora Longgom (Departemen Matematika, 2024)
Students must prioritize learning outcomes. In reality, the mathematics learning results of eighth grade students at SMPN 43 Padang are still below standard. The solution provided is the Think Talk Write (TTW) cooperative model. The research methodology used includes descriptive research and quasi-research, with Nonequivalent Posttest-Only Control Group Design. By analyzing the learning outcomes test using the t-test, it shows a P-value of 0.009 at the significance level. This study involved all eighth grade students at SMPN 43 Padang for TP 2023/2024. Based on data analysis, learning outcomes through the Think Talk Write (TTW) type cooperative learning model are higher than students who learn using the direct learning model.Keywords– Learning outcomes, Cooperative Learning, Think Talk Write